Candidate radio supernova remnants observed by the GLEAM survey over 345° < l < 60° and 180° < l < 240°. (2019) - Hurley-Walker, N.; Gaensler, B. M.; Leahy, D. A.; Filipović, M. D.; Hancock, P. J.; Franzen, T. M. O.; Offringa, A. R.; Callingham, J. R.; Hindson, L.; Wu, C.; Bell, M. E.; For, B.-Q.; et al.
Abstract: We examined the latest data release from the GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey covering 345° < l < 60° and 180° < l < 240°, using these data and that of the Widefield Infrared Survey Explorer to follow up proposed candidate Supernova Remnant (SNR) from other sources. Of the 101 candidates proposed in the region, we are able to definitively confirm ten as SNRs, tentatively confirm two as SNRs, and reclassify five as H ii regions. A further two are detectable in our images but difficult to classify; the remaining 82 are undetectable in these data. We also investigated the 18 unclassified Multi-Array Galactic Plane Imaging Survey (MAGPIS) candidate SNRs, newly confirming three as SNRs, reclassifying two as H ii regions, and exploring the unusual spectra and morphology of two others.